1999
DOI: 10.1002/(sici)1097-4547(19990601)56:5<506::aid-jnr6>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Reinnervation of denervated lumbar ventral roots and their target muscle by thoracic spinal motoneurons via an implanted nerve autograft in adult rats after spinal cord injury

Abstract: Intraspinally implanting a nerve autograft (NAG) to promote axonal regeneration toward periphery was investigated as a surgical treatment for spinal cord injury in adult rats. Fifteen animals underwent a left hemisection of the spinal cord at T12 level and an intradural section of all ipsilateral lumbar ventral roots. In repaired animals (n = 9), the electrophysiologically selected left L3 and L4 lumbar ventral roots supplying the quadriceps muscle were anastomosed to a NAG. The NAG was taken from the right pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…42 A second study showed partial recovery of limb function following the transfer of multiple intercostal nerves to multiple lumbar nerve roots in the rat. 24 A variant of a spinal cord bypass without using nerve transfers has been developed in rats 23,24 and later in primates. 20,21 In this model, the proximal terminus of peripheral nerve autografts is implanted into the ventral horn of the spinal cord below the level of injury, whereas the distal ends are anastomosed to the lumbar ventral nerve roots.…”
Section: Spinal Cord Bypass: Animal Studiesmentioning
confidence: 99%
“…42 A second study showed partial recovery of limb function following the transfer of multiple intercostal nerves to multiple lumbar nerve roots in the rat. 24 A variant of a spinal cord bypass without using nerve transfers has been developed in rats 23,24 and later in primates. 20,21 In this model, the proximal terminus of peripheral nerve autografts is implanted into the ventral horn of the spinal cord below the level of injury, whereas the distal ends are anastomosed to the lumbar ventral nerve roots.…”
Section: Spinal Cord Bypass: Animal Studiesmentioning
confidence: 99%
“…Our protocol is an extension of the nerve bypass approach that was pioneered by David and Aguayo (1981) and that was modified recently by Gauthier et al (2002). Liu et al (1999) have also used this approach to promote motor axon growth directly to muscles paralyzed by spinal lesion. Each of these groups used an isolated peripheral nerve segment as a conduit to direct axons from one spinal cord level to another.…”
Section: T13 Nerve Insertion Procedures Has Advantages Over Other Bridmentioning
confidence: 99%
“…In the first case, a peripheral nerve autograft is used as source. This technique was first introduced by Aguayo [3] and recently demonstrated by Liu et al [110] as well as Sauvé et al [135]. Electrophysiologically selected L3 and L4 lumbar ventral roots supplying the quadriceps muscle were anastomosed to a nerve autograft (NAG).…”
Section: Establishing Functional Synaptic Connectionsmentioning
confidence: 99%